The Holy Spirit in the Theological Work of Michael Servetus The Spirit of Unity, or from Accident to Substance - Schulte am Hülse, Christine (Church History and Religious Culture, 2021)
This article examines the pneumatology in the theological works of the "heretic" Michael Servetus, which so far has received limited attention in research. This is worthwhile, since Servetus developed two answers to the question of what the Holy Spirit is: on the one hand, a movement of God in the human spirit understood as a divine accident of God; or, on the other, even the divine substance itself, which is physiologically incorporated by humans. The occasion and the focus of this article are therefore the perception and the discussion of these two pneumatological approaches and their most significant differences. Both approaches are outlined in their main features and explained in their respective contexts. Nevertheless, these separate analyses will also be related to each other in a comparative fashion, so that a fundamental moment of Servetus' entire pneumatology can be identified: the constitution and mediation of unity between God and creation.
CRIS-Team WoS Importer:2021-08-20